Biomechanical defects and rescue of cardiomyocytes expressing pathologic nuclear lamins. Issue 6 (8th February 2018) - Laurini, Erik; Martinelli, Valentina; Lanzicher, Thomas; Puzzi, Luca; Borin, Daniele; Chen, Suet Nee; Long, Carlin S; Lee, Patrice; Mestroni, Luisa; Taylor, Matthew R G; Sbaizero, Orfeo; Pricl, Sabrina
Abstract: Aims: Given the clinical impact of LMNA cardiomyopathies, understanding lamin function will fulfill a clinical need and will lead to advancement in the treatment of heart failure. A multidisciplinary approach combining cell biology, atomic force microscopy (AFM), and molecular modeling was used to analyse the biomechanical properties of human lamin A/C gene ( LMNA) mutations (E161K, D192G, N195K) using an in vitro neonatal rat ventricular myocyte model. Methods and results: The severity of biomechanical defects due to the three LMNA mutations correlated with the severity of the clinical phenotype. AFM and molecular modeling identified distinctive biomechanical and structural changes, with increasing severity from E161K to N195K and D192G, respectively. Additionally, the biomechanical defects were rescued with a p38 MAPK inhibitor. Conclusions: AFM and molecular modeling were able to quantify distinct biomechanical and structural defects in LMNA mutations E161K, D192G, and N195K and correlate the defects with clinical phenotypic severity. Improvements in cellular biomechanical phenotype was demonstrated and may represent a mechanism of action for p38 MAPK inhibition therapy that is now being used in human clinical trials to treat laminopathies.